2018
DOI: 10.1016/j.taap.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Differences in statin associated neuroprotection corresponds with either decreased production of IL-1β or TNF-α in an in vitro model of neuroinflammation-induced neurodegeneration

Abstract: 3-Hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitors (statins) have been associated with conflicting effects within the central nervous system (CNS), with underlying mechanisms remaining unclear. Although differences between individual statins' CNS effects have been reported clinically, few studies to date have compared multiple statins' neuroprotective effects. This study aimed to compare six statins (atorvastatin, fluvastatin, pitavastatin, pravastatin, rosuvastatin, simvastatin; 0-100 μM) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 73 publications
3
27
0
1
Order By: Relevance
“…In inflammationrelated neurodegenerative disease (Lei et al 2018), mitochondrial fission is activated and contributes to mitochondrial oxidative stress. Additionally, IL-1β-mediated neurodegeneration is associated with mitochondrial oxidative stress and mitochondrial depolarization (McFarland et al 2018). Moreover, inflammation-induced depressive-like behavior is related to mitochondrial abnormalities (Chen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In inflammationrelated neurodegenerative disease (Lei et al 2018), mitochondrial fission is activated and contributes to mitochondrial oxidative stress. Additionally, IL-1β-mediated neurodegeneration is associated with mitochondrial oxidative stress and mitochondrial depolarization (McFarland et al 2018). Moreover, inflammation-induced depressive-like behavior is related to mitochondrial abnormalities (Chen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have shown that a combination of statins (atorvastatin, fluvastatin, pitavastatin, pravastatin, rosuvastatin, and simvastatin) may prevent neuroinflammation-mediated neurodegeneration. The mechanism may be through statin downregulated autophagy to provide neuroprotective effects [ 65 ].…”
Section: Ampk-associated Therapeutic Effects Of Statinsmentioning
confidence: 99%
“…This study examined rosuvastatin, which exhibits better potency than other statins (Lopez, 2003;Karlson et al, 2016). The effect of rosuvastatin on autophagy in cancer and neuroinflammation has been studied (Zeybek et al, 2011;McFarland et al, 2018). Previous study has shown that atorvastatin, one of the statin family, protects…”
Section: Discussionmentioning
confidence: 99%